Aligning State-Owned Enterprises with Constitutional Values: The Case of Indonesian BUMN Holding Companies - Ernawati, Elisatin; Suhariningsih, Sri; Kusumadara, Afifa; Santoso, Budi (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2023)
This study examines the relationship between Indonesia's economic constitution and the legal framework governing State-Owned Enterprises (BUMN) holding companies. The research analyzes the alignment of BUMN operations with constitutional ideals of welfare and social justice, based on the principles of the 1945 Constitution and the Limited Liability Company Law. The text highlights the discrepancies between theoretical principles and practical implementations, specifically in the areas of corporate governance, ethical conduct, and fair economic distribution. The investigation focuses on how these discrepancies manifest in BUMN operations, their impact on stakeholders, and the wider socio-economic implications for Indonesia. The study emphasizes the need for specific regulations that are tailored to the unique structural and operational characteristics of BUMN holding companies. Recommendations include improving oversight, increasing transparency, and strengthening accountability mechanisms. These measures are essential for aligning BUMN practices with constitutional mandates, ensuring operational efficiency and competitiveness, and making significant contributions to national socio-economic progress.